Weighted estimation and reduction of influence of bounded perturbations in descriptor control systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.925.51; 681.5.03 For a class of linear descriptor systems, we establish new criteria for existence of control laws that provide the asymptotic stability and a prescribed estimate for the weighted damping level of bounded disturbances. We suggest a method of generalized H_∞-optimization of descriptor systems with controlled and observed outputs. The main computational procedures of the suggested algorithm are reduced to solving linear and quadratic matrix inequalities with additional rank constraints. We also give an example of a descriptor control system for an electrical circuit.